Family social support during incarceration: implications for health upon release - Chantal Fahmy; Alexander Testa (Scientific Reports)
Abstract Incarceration is associated with adverse physical and mental health that are often brought to light during reentry into the community, particularly in the immediate period following release. Social support, specifically from family members, has been identified as a key protective factor that may promote health and reintegration success among formerly incarcerated individuals. However, less is known about how specific types of family support—emotional and instrumental—relate to health outcomes following release from incarceration. The current study uses data from 517 individuals incarcerated in a large Texas prison, surveyed before and approximately one month after release, to examine the relationship between family support and self-rated physical and mental health. Logistic regression models revealed that strong emotional family support was significantly associated with better self-rated physical health and mental health one month post-release. Additionally, strong instrumental family support predicted better mental health but not physical health among respondents. These findings highlight the crucial role of emotional and instrumental familial support systems in fostering and reducing health disparities and promoting equity among justice-impacted populations.